Förtroende och trygghet : En enkätstudie om trygghet i Luleå kommun samt förtroende för rättsväsendet. - Hallikainen, Andreas (2012)
Confidence in the judiciary and security in society are two things that are basic to afunctioning and non-corrupt society. The purpose of this thesis was to investigate theinhabitant’s of Luleå Municipality confidence in the judiciary and to measure insecurity amongits inhabitants. The following questions were posed: “How big is the confidence inthe judiciary as a whole, for individual authorities and the way they perform differenttasks?” and “How widespread is the insecurity in Luleå Municipality and how common isit that people worry about different types of crime?” A quantitative questionnaire wasconducted with men and women in different age groups, all inhabited in Luleå Municipality.The results showed that women worried more extensively than men did, especially with regardto concerns about violent crime, while men had a higher concern for crimes related to theircar. The results also imply that the respondents' confidence was highest for the police, whilethe court was the lowest trustworthy authority. Moreover, the older respondents felt safest ofall groups regarding assault, a result that differs from national studies. Validerat; 20120102 (anonymous)